Uso da posição canguru em domicílio: percepção de mães de recém-nascidos de risco - Legnaro, Bárbara de Souza Coelho (2021)
The kangaroo position is a care strategy indicated for children born preterm, as well as for those with low birth weight. It is one of the structuring of the Kangaroo Method, but it can be adopted in isolation. The use of position is recognized as a low-cost neonatal care technology with relevant outcomes for the child's health, survival and development, as well as favoring the parent-child bond and parenthood. Its use in Brazil is concentrated in the hospital environment, although it is also recommended for times after hospital discharge. To analyze the perception of mothers of preterm and/or low birth weight children regarding the use of the kangaroo position at home. This is a qualitative research, developed through an unstructured interview, under the references of Symbolic Interactionism and Thematic Analysis. It presents the analysis of interviews with 10 women, mothers of children born prematurely and/or underweight, who incorporated the use of the kangaroo position in their daily lives, for at least one hour a day, in line with the model's recommendations. All women resided in the Center-East region of the state of São Paulo. The themes 'Apprehensive waiting to take care of the child', 'Arrangements and feelings in using the kangaroo position' and 'Health services and faith' organize the presentation of the analysis developed. In these revealed that from the beginning of the pregnancy, when they discover it to be a risky pregnancy, the stories of loss of children previously experienced and birth unexpectedly, bring these women feelings of fear and anguish with the pregnancy outcome, but at the same time of joy and relief upon receiving the child. The kangaroo position is conceived as a proper care strategy for the child's condition, an understanding that supports their choice to use it. Social interactions are presented, especially throughout the times experienced in the child's hospitalization, which lead women to question their skills in caring for the child, as well as attributing feelings that together bring apprehension to the assumption of this care. In rooming-in there is no thematization of the kangaroo position, while in the neonatal unit it is present. During the practice of the kangaroo position at home, they perceive the benefits, with emphasis on empowerment and security for care and promoting the inclusion of the child's partner/father in it. For the use of adjustments in the family routine is a differential and having the support of the primary care network makes all the difference in the effectiveness of the pareral care and in the use of the kangaroo position, but the proximity of primary care professionals/health services is incipient to these women who demonstrate the desire for this support. the professional support in this context indicates weakness regarding the consideration of the kangaroo position in the care of these women, children and families, since the prenatal period. Nursing was mentioned in the neonatal unit and in the person of the visiting nurses, with indications that it is urgent to expand and qualify its presence and support, which makes the passage through the pueperal period to be less lonely and painful, promoting the achievement of comfort and satisfaction to these women, who have in the use of the kangaroo position a propellant.